PENGARUH CITRA DAYA TARIK WISATA TERHADAP KEPUASAN PENGUNJUNG DAN IMPLIKASINYA PADA LOYALITAS PENGUNJUNG DI DAGO DREAMPARK - Azka Fania Kharima, Azka (2020)
The purposes of this research are to analyze effect among tourist attraction images, tourist satisfaction and tourist loyalty. This research analyzed direct and indirect effects of tourist attraction images on tourist loyalty. Methode used of this research was quantitative approach with 250 respondents. accidental sampling was used with a population of visitors whom attended Dago Dreampark. Pilot test on 50 respondent was used. Path analysis was followed afterward. Result of this study shows that destination images effects tourist loyalty indirectly by tourists' satisfactions. This research gives contribution to management in enhancingtourist loyalty and able to be references for the next research.